Eosinophil function in adipose tissue is regulated by Krüppel-like factor 3 (KLF3) - Knights, Alexander J.; Vohralik, Emily J.; Houweling, Peter J.; Stout, Elizabeth S.; Norton, Laura J.; Alexopoulos, Stephanie J.; Yik, Jinfen. J.; Mat Jusoh, Hanapi; Olzomer, Ellen M.; Bell-Anderson, Kim S.; North, Kathryn N.; Hoehn, Kyle L.; et al. (Springer Nature, 2020)
The conversion of white adipocytes to thermogenic beige adipocytes represents a potential mechanism to treat obesity and related metabolic disorders. However, the mechanisms involved in converting white to beige adipose tissue remain incompletely understood. Here we show profound beiging in a genetic mouse model lacking the transcriptional repressor Krüppel-like factor 3 (KLF3). Bone marrow transplants from these animals confer the beige phenotype on wild type recipients. Analysis of the cellular and molecular changes reveal an accumulation of eosinophils in adipose tissue. We examine the transcriptomic profile of adipose-resident eosinophils and posit that KLF3 regulates adipose tissue function via transcriptional control of secreted molecules linked to beiging. Furthermore, we provide evidence that eosinophils may directly act on adipocytes to drive beiging and highlight the critical role of these little-understood immune cells in thermogenesis